PHD1 regulates p53-mediated colorectal cancer chemoresistance - Deschoemaeker, Sofie; Di Conza, Giusy; Lilla, Sergio; Martín-Pérez, Rosa; Mennerich, Daniela; Boon, Lise; Hendrikx, Stefanie; Maddocks, Oliver DK; Marx, Christian; Radhakrishnan, Praveen; Prenen, Hans; Schneider, Martin; et al. (EMBO molecular medicine, 2015)
Overcoming resistance to chemotherapy is a major challenge in colorectal cancer (CRC) treatment, especially since the underlying molecular mechanisms remain unclear. We show that silencing of the prolyl hydroxylase domain protein PHD1, but not PHD2 or PHD3, prevents p53 activation upon chemotherapy in different CRC cell lines, thereby inhibiting DNA repair and favoring cell death. Mechanistically, PHD1 activity reinforces p53 binding to p38α kinase in a hydroxylation-dependent manner. Following p53-p38α interaction and chemotherapeutic damage, p53 can be phosphorylated at serine 15 and thus activated. Active p53 allows nucleotide excision repair by interacting with the DNA helicase XPB, thereby protecting from chemotherapy-induced apoptosis. In accord with this observation, PHD1 knockdown greatly sensitizes CRC to 5-FU in mice. We propose that PHD1 is part of the resistance machinery in CRC, supporting rational drug design of PHD1-specific inhibitors and their use in combination with chemotherapy.
Gesehen am 13.01.2021